Translation and Cross-Cultural Adaptation of the Pediatric Outcomes Data Collection Instrument into the Italian Language - Giovanni Trisolino; Stefano Stallone; Paola Zarantonello; Andrea Evangelista; Manila Boarini; Jacopo Faranda Cordella; Luca Lerma; Luisa Veronesi; Cosma Caterina Guerra; Luca Sangiorgi; Giovanni Luigi Di Gennaro; Renato Maria Toniolo (MDPI AG, 2022)
(1) Background: The Pediatric Outcomes Data Collection Instrument (PODCI) is an English-language questionnaire specifically designed to assess health-related quality of life in children and adolescents with musculoskeletal disorders. This scoring system has been translated into several languages. Given the lack of an Italian version of the PODCI, this study aimed to translate, cross-culturally adapt, and assess the psychometric properties of the PODCI score in the Italian pediatric population. (2) Methods: The PODCI questionnaire was culturally adapted to Italian patients in accordance with the literature guidelines. The study included 59 participants from a single orthopedic institution who underwent orthopedic surgery for various skeletal conditions. The questionnaire was administered to participants at multiple time-points (T0, T1, T2). Internal consistency was evaluated using Cronbach's alpha. Reproducibility was assessed using the intraclass correlation coefficient (ICC) between T0 and T1 assessment. Criterion validity was assessed using Spearman's correlation coefficients between PODCI and the Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS). Responsiveness was evaluated by the difference between T0 and T2 using the effect size (ES) and the standardized response mean (SRM) calculation. (3) Results: Cronbach's alpha was acceptable in both the self- and parent-reported versions with values of 0.78 (0.68-0.90) and 0.84 (0.60-0.92), respectively. The ICC fluctuated between 0.31 and 0.89 for self-reported and 0.49 to 0.87 for pediatrics. The Spearman's r showed a moderate correlation between HSS Pedi-FABS and the "Sport & Physical Functioning" and "Global Functioning" domains. ES and SRM varied from small to moderate across all the domains. (4) Conclusions: This study demonstrates that the Italian version of the PODCI, translated following the international standardized guidelines, is reliable, valid, and responsive in pediatric patients who underwent orthopedic surgery.